2023
DOI: 10.1177/15210251231210855
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Stress Influence Students’ Campus Climate Perceptions and Sense of Belonging?

Thomas Zimmerman,
Eugene T. Parker

Abstract: Studies of financial stress, college debt, campus climate, and sense of belonging have each been conducted to better understand student retention and persistence, but few studies have explored the relationship between these variables and student outcomes. Researchers have found that financial need has a negative effect on student's psychological experiences, while other studies have explored the impact of general stress in college on psychological constructs, such as campus climate. However, little evidence ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Moore et al [12], also found that students encountering financial stress struggle to handle interactions with wealthier peers, frequently resulting in feelings of isolation and embarrassment. Additionally, financial stress reduces students' motivation, influences their educational choices, disrupts their sense of belonging, and alters their perceptions of the campus environment, leading to school dropout and reduced retention rates [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al [12], also found that students encountering financial stress struggle to handle interactions with wealthier peers, frequently resulting in feelings of isolation and embarrassment. Additionally, financial stress reduces students' motivation, influences their educational choices, disrupts their sense of belonging, and alters their perceptions of the campus environment, leading to school dropout and reduced retention rates [15,16,17].…”
Section: Introductionmentioning
confidence: 99%